HUBUNGAN PENDIDIKAN AKHLAK DI SEKOLAH DENGAN KECERDASAN EMOSIONAL ANAK 5-6 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU KECAMATAN MARPOYAN DAMAI - Wina Annisa; Daviq Chairlsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the level correlation of education achievement in school with the emotional intelligence of children 5-6 years in TK Negeri Pembina 3 Pekanbaru city which amounted to 122 children. The method used in this study is a quantitative correlation to see the relationship between the free variables by binding. The data collection techniques used are by observation. The data analysis technique uses the Person Product Moment correlation test with the IBM SPSS for Windows Ver. 23 program. From the results of the known research studies are in medium category with a percentage value of 67.38% and the level of emotional intelligence is in medium category with a percentage value of 67.13%. Based on the results of the hypothesis test obtained there is a positive and significant relationship between the emotional intelligence of early childhood 5-6 years in KINDERGARTEN State Pembina 3 Kota Pekanbaru. This can be known from the value of the correlation coefficient of = 0.821 and the value of the coefficient of determination generated by KD = x 100% = 0.821 x 100% = 67.40% has the meaning that moral education has an influence of 67, 40% against of education achievement.Key Words: Correlation, Education Achievement, Emotional Intelligence